ANALISIS PENGARUH KUALITAS LAYANAN, FASILITAS, CITRA RUMAH SAKIT, KEPUASAN PASIEN DALAM RANGKA MENINGKATKAN LOYALITAS PASIEN (Studi Pada Pasien Rawat Inap RSUD Tugurejo Semarang) - Sharon, Lyrissa Gisela; Santoso, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2017)
The background of this research is the increasing number of complaints of inpatients, especially on the quality of services and facilities. The growing number of complaints leads to dissatisfaction and will affect patient loyalty. The purpose of this study is to determine the effect of service quality, facilities hospital image, patient satisfaction on the loyalty of RSUD Tugurejo’s Semarang inpatients. Technique that used in this research is Non-Probability Sampling with Purposive Sampling approach, which has ever used inpatient services of RSUD Tugurejo in 2016, who is appropriate to be a sample. The collection of data obtained through 182 inpatients, with the aim of knowing the responses of respondents on the variables studied by questionnaire tool, using Likert 1-10 scale. Data analysis and interpretation techniques using SEM (Structural Equation Modeling), according to the model developed in this study, the operation through Amos version 22.0 program. The results showed that service quality has a positive and significant effect on hospital image, service quality has a positive and significant effect on patient satisfaction, service quality has a positive and significant effect on patient loyalty. Facilities has a positive and significant effect on service quality, facilities has a positive and significant effect on hospital image, facilities has a positive and significant effect on patient satisfaction. Hospital image has a positive and significant effect on patient loyalty. Patient satisfaction has a positive and significant influence on patient loyalty